STUDY REGARDING THE IMPACT OF PHYSICAL EDUCATION AND SPORT ON STUDENTS LIFE FROM UNIVERSITY "LUCIAN BLAGA" SIBIU - Ioan Sabin SOPA; Marcel POMOHACI (Editura Universităţii din Oradea, 2016)
In this research, we tried to discover the motivations considered by the students decisive for active participation in the motor activities proposed within the hours of physical activity and sport. The study had as main research method the survey of views and research sample included a total of 100 students from the University "Lucian Blaga" from Sibiu. Research findings showed that the main motivation of students to practice motor activities were keeping or maintaining optimal health, the need for relaxation or stress relieving, maintaining a physically, mentally, emotionally and socially balance, the attractiveness of motor activities, promoting values in the sphere of socialization, finding new friends, communication, socialization. Gender differences show that opinions are divided, male students consider physical and social motivations as most important while female students consider as exponential for the motor activities the mental and sanogenic effects.